2018
DOI: 10.3390/toxins10030111
|View full text |Cite
|
Sign up to set email alerts
|

UDP-Glucosyltransferases from Rice, Brachypodium, and Barley: Substrate Specificities and Synthesis of Type A and B Trichothecene-3-O-β-d-glucosides

Abstract: Trichothecene toxins are confirmed or suspected virulence factors of various plant-pathogenic Fusarium species. Plants can detoxify these to a variable extent by glucosylation, a reaction catalyzed by UDP-glucosyltransferases (UGTs). Due to the unavailability of analytical standards for many trichothecene-glucoconjugates, information on such compounds is limited. Here, the previously identified deoxynivalenol-conjugating UGTs HvUGT13248 (barley), OsUGT79 (rice) and Bradi5g03300 (Brachypodium), were expressed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 56 publications
1
21
0
2
Order By: Relevance
“…Aflatoxin dialdehyde aldo-keto reductase AKR7A1 (Figure 2 [15,16], Table 1 [17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58]) was isolated from rat liver, and its structure in complex with NADP + was solved [59]. This enzyme is assumed to reduce both aldehyde groups of dialdehyde of hydroxy aflatoxin B 2a , forming from 8,9-dihydrodiol aflatoxin B 1 , resulted in dihydroxy derivative.…”
Section: Aflatoxinsmentioning
confidence: 99%
“…Aflatoxin dialdehyde aldo-keto reductase AKR7A1 (Figure 2 [15,16], Table 1 [17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58]) was isolated from rat liver, and its structure in complex with NADP + was solved [59]. This enzyme is assumed to reduce both aldehyde groups of dialdehyde of hydroxy aflatoxin B 2a , forming from 8,9-dihydrodiol aflatoxin B 1 , resulted in dihydroxy derivative.…”
Section: Aflatoxinsmentioning
confidence: 99%
“…Of more importance were differences in mycotoxin content between genotypes like Tim (low DON content) and Bessin (high DON content) or Keely (low DON content) and Scorpion (high DON content) with similar PH, AR, and BBCH in Panel 2. Possible reasons for such differences were detoxification of DON (Michlmayr et al, 2018) or a variation in trichome-type cells, which were found to be related to Fusarium ingress and resistance responses in barley (Imboden, Afton, & Trail, 2018).…”
Section: Flowering Traits and Fusarium Avoidancementioning
confidence: 99%
“…The Bradi5g03300 UGT has recently been shown to be able to conjugate different mycotoxins belonging to trichothecenes, either type A or type B, in recombinant protein assays (Michlmayr et al, 2018). Future studies investigating whether this novel wheat UGT also exhibits a level of substrate flexibility will be of special interest, in particular to estimate its ability to be used as a source a resistance against a wider range of Fusarium sp.…”
Section: Discussionmentioning
confidence: 99%